2006
DOI: 10.1021/ja062364i
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies of Complex Immunostimulants from Quillaja saponaria:  Synthesis of the Potent Clinical Immunoadjuvant QS-21Aapi

Abstract: QS-21 is one of the most promising new adjuvants for immune response potentiation and dose-sparing in vaccine therapy given its exceedingly high level of potency and its favorable toxicity profile. Melanoma, breast cancer, small cell lung cancer, prostate cancer, HIV-1, and malaria are among the numerous maladies targeted in more than 80 recent and ongoing vaccine therapy clinical trials involving QS-21 as a critical adjuvant component for immune response augmentation. QS-21 is a natural product immunostimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 45 publications
5
81
0
1
Order By: Relevance
“…49 The parent D-fucose (30) was first transformed into the 2,4-diol 31 by anomeric allylation and regioselective benzylation via the stannylene acetal intermediate. The equatorial 2-OH group of 31 was masked as its TBS ether, while the 4-OH group was acetylated, thus yielding a fully orthogonally protected intermediate 32.…”
Section: Synthesis Of Aglyconesmentioning
confidence: 99%
See 2 more Smart Citations
“…49 The parent D-fucose (30) was first transformed into the 2,4-diol 31 by anomeric allylation and regioselective benzylation via the stannylene acetal intermediate. The equatorial 2-OH group of 31 was masked as its TBS ether, while the 4-OH group was acetylated, thus yielding a fully orthogonally protected intermediate 32.…”
Section: Synthesis Of Aglyconesmentioning
confidence: 99%
“…59 In 2006, Gin and coworkers reported that global deprotection of the QS-21A api skeleton 64 under various conditions of acidic hydrolysis-hydrogenolysis yielded only trace amount of QS-21A api (66) because the acid-mediated cleavage of the isopropylidene group installed in the apiose moiety could not be effected without compromising the glycosidic linkages (Scheme 13). 49 However, when the isopropylidene group was substituted by a benzylidene group (compound 65), the synthesis of QS-21A api could be successfully completed.…”
Section: Protecting-group Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reagent TPAP/NMO/PMS/ CH 3 CN effected a diol to lactone step in the synthesis of the antitumour agent entclavilactone B [358] and the antileukemic agents (−)-eriolangin and (−)-eriolanin [359]. During synthesis of the protein phosphatase inhibitor okadaic acid three oxidations with TPAP/NMO/PMS/CH 2 Cl 2 were used, two of primary alcohol to aldehydes and one of a diol to a lactone [109], and in the synthesis of the immunoadjuvant QS-21A api a diol-to-lactone step is involved [360], as in the case of the lypophilic macrolide rapamycin (cf. 1.11) [181].…”
Section: Specific Examplesmentioning
confidence: 99%
“…The major aglycone is quillaic acid. A particular feature of Quillaja saponins are the aldehyde group attached to C-4, and a structurally elaborate branched acyl moiety with a terminal L-arabinose [146].…”
Section: Quillaja Saponinsmentioning
confidence: 99%